Клиническая картина слизистой полости рта у пациентов с ВИЧ-инфекцией до и после комплексного лечения - Азатян, В. Ю.; Есаян, Л. К. (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
Ժամանակակից պրակտիկ ստոմատոլոգիայի կարևոր խնդիրներից են բերանի խոռոչի լորձաթաղանթի (ԲԽԼ) հիվանդությունների ախտորոշման, կանխարգելման, բուժման հիմնահարցերը: Աշխատանքի նպատակն է ուսումնասիրել ՄԻԱՎ վարակով բուժառուների բերանի խոռոչի լորձաթաղանթի կլինիկական պատկերը համալիր բուժումից առաջ և հետո: Հետազոտվել է ՄԻԱՎ վարակով 90 բուժառու համալիր բուժումից առաջ և հետո, որոնցից 9-ը (10%) կանայք էին, իսկ 81-ը (90%)՝ տղամարդիկ, որոնց միջին տարիքը` 45,2 ± 8,34, ինչպես նաև հսկիչ խմբում 100 մարդ՝ 38 (38%) կին և 62 (62%) տղամարդ, միջին տարիքը՝ 37,99±16,66: Հսկիչ խումբը կազմում են ԲԽԼ ախտահարումներ ունեցող անձինք՝ առանց ՄԻԱՎ վարակի: Among the important problems of modern practical dentistry, the issues of improving the diagnosis, prevention, treatment of diseases the oral mucosa (OM). The aim of the work was to study the clinical picture of the oral cavity in patients with HIV infection before and after complex treatment. 90 patients with HIV infection were examined before and after complex treatment: which 9 (10%) were women and 81 (90%) were men. The average age of the patients was 45.2 ± 8.34, as well as 100 patients in the control group: 38 (38%) women and 62 (62%) men. The average age of patients in the control group was 37.99±16.66. The control group consisted of individuals with lesions of the OM without HIV infection. To study the dental status, patients' complaints and data from a clinical examination of the oral cavity were taken into account, which included: external examination of the lips and corners of the mouth, assessment of the condition of various parts of the oral mucosa. Thus, in a comparative study of lesions of the oral cavity before and after complex treatment for HIV infection, it was found that the main pathognomonic symptoms reliably undergo dynamics towards improvement and are detected with less frequency.
Keywords: Клиническая медицина